Karakteristik Pemanpatan Tanah Gambut Dengan Variasi Serat - Wulandari, Deny; Fatnanta, Ferry; Nugroho, Soewignjo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A peat soil has different characteristics compared to clay, therefore some consolidation tests are needed to obtain a proper compression method when construction are located on peat soils. The purpose of this research was to determine the compression characteristics of peat soil with fiber variation based on Gibson and Lo (1961) method and laboratory testing. This research used amorphous peat, a samples which taken from Tambang, Kampar. The first sample is undisturbed, and the second with zero fiber, 30 % fiber and 60 % fiber. The equipment used consist of modified consolidometer, with a diameter and height are 15 cm. The load were applied 10 kPa, 20 kPa, 40 kPa, 80 kPa and 160 kPa. Some loads were added every 14 days. The result showed that water content has no influence to settlement, and samples with great amount of water content has low strain. Samples with high fiber content and low unit weight, i.e. 60% of fiber content produce the highest strain. Therefore, unit weight is a very crucial point in determining settlement in this research. Square root of time method can’t be used on peat due to the different from settlement vs time root curve. The void ratio vs strain curve formed in concave shape due to the macropores and micropores inside the peat. On real condition and 30% of fiber samples, the time to reach 90 % of compressibility were reduced along with enhanced loads, the fiberless and 60 % of fiber samples were increased along with enhanced loads. Gibson and Lo method can’t be used on amorphous peat. Hence, it needs to be corrected with primary compression parameters (a), secondary compression parameters (b) and .Keywords: Peat, Amorphous, Fiber Content, Consolidometer